Planktic foraminiferal proxy development and application to paleoceanographic change in the Southwest Pacific Ocean - Marr, Julene (2013)
This thesis investigates the use of foraminiferal calcite geochemical and physical properties as paleoceanographic proxies, to improve identification of past climatic change and provide a more quantitative basis for forecasts of future climate. I have developed and used these proxies on a high resolution, well-dated marine sediment core, MD97 2121 from north of the Subtropical Front (STF) off the eastern central North Island of New Zealand to determine paleoceanographic changes in the South Pacific Gyre since the last glacial period, 25 ka to present. Various analytical methods to measure foraminiferal calcite trace element geochemistry were first investigated using core top samples. Two main analytical techniques were deployed; “pseudo” solution- or laser ablation-based ICPMS analysis. Ratios tested include Mg/Ca, Sr/Ca, Ba/Ca, Zn/Ca, Mn/Ca and Al/Ca. Trace element/calcium ratios Mg/Ca and Sr/Ca values were consistent between these methods, provided that currently recommended ‘Mg-cleaning’ protocols were followed for solution-based measurements. However, discrepancies of up to an order-of-magnitude for Zn/Ca, Mn/Ca and Ba/Ca occurred between solution and laser ablation-based measurements if both oxidative and reductive cleaning techniques were not employed prior to solution-based analysis. Using down-core trace element values Mg/Ca, Zn/Ca, Mn/Ca and Ba/Ca from MD97 2121, coupled with modern core top and plankton-tow samples, multiple geochemical proxies for the SW Pacific Ocean were developed and/or tested. Results suggest that Zn/Ca may act as (i) a surface water mass tracer, in this case differentiating between subtropical and subantarctic surface waters and (ii) a proxy for nutrients. Mg/Ca and Zn/Ca values from different test chambers in Globigerina bulloides were also found to reliably re-construct surface ocean temperature and nutrient stratification. Using these new proxies, coupled with oxygen isotopes, standard Mg/Ca paleothermometry and foraminiferal assemblage data, I show that surface water nutrient ...